Effect of organic attapulgite on properties of SBS modified asphalt waterproofing membranes. (19th December 2022) - Zeng, Shangheng; Gong, Xingyu; Han, Xiaobin; Xu, Shi; Xu, Jinghui; Li, Xiong; Yu, Jianying
Highlights: OATP enhances high temperature performance of SMAWM. Compared with ATP, OATP has less influence on low-temperature performance of SMAWM. OATP significantly improves thermal and UV aging resistance of SMAWM. Abstract: In order to improve the aging resistance of styrene butadiene styrene (SBS) modified asphalt waterproofing membranes (SMAWM), in this study, vinyltriethoxysilane grafted attapulgite (VTES-g-ATP) and octadecyl-dimethyl-benzyl-ammonium chloride intercalated attapulgite (ODBA-i-ATP) was prepared, respectively. The effects of VTES-g-ATP and ODBA-i-ATP on properties of SMAWM before and after thermal and ultraviolet aging were investigated. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and loss on ignition test indicated that the cationic surfactant octadecyl-dimethyl-benzyl-ammonium chloride (ODBA) was intercalated into the porous structure of attapulgite (ATP), while the coupling agent vinyltriethoxysilane (VTES) was grafted on the surface of ATP. The water contact angles of ATP, VTES-g-ATP and ODBA-i-ATP were 0°, 50.25° and 72.25°, respectively, revealing VTES-g-ATP and ODBA-i-ATP had better hydrophobicity. Compared to ATP, VTES-g-ATP and ODBA-i-ATP effectively improved the softening point and viscosity and had less effect on the low-temperature flexibility of SMAWM. The results of thermal and ultraviolet aging showed that VTES-g-ATP and ODBA-i-ATP were superior to ATP in enhancing aging resistance of SMAWA, particularly ODBA-i-ATP. FTIR analysis showed that ATP, VTES-g-ATP and ODBA-i-ATP effectively inhibited the oxidative polycondensation of asphalt and the degradation of SBS. Considering the balance of physical properties and aging resistance of modified SMAWM, the ODBA-i-ATP was more suitable as an additive for SMAWM, and the optimal dosage of ODBA-i-ATP in SMAWM is 3.0 wt%.